The effect of extrusion processing on the physiochemical properties of extruded orange pomace - Huang, Ya-Ling; Ma, Ya-Sheng (Food chemistry, 2016)
•Optimum extrusion processing of SDF from orange pomace has been studied.•Extrusion process enhanced the yield of SDF in orange pomace.•Extrusion process improved physicochemical properties of orange pomace.•Increase in SDF fraction was due to a redistribution of IDF to SDF. Soluble dietary fibre (SDF) is considered the most effective fraction of dietary fibre (DF) for human health. In this study, extrusion technology was applied to enhance the SDF obtained from orange pomace, a byproduct of juice extraction containing a high level of DF. The pomace was processed in a single-screw extruder at various barrel temperatures (X1; 115–135°C), feed moistures (X2; 10–18g/100g), and screw speeds (X3; 230–350rpm). Based on response surface methodology, the optimum extrusion conditions, which produced a maximum SDF value of 30.36%, were as follows: barrel temperature, 129°C; feed moisture, 15%; and screw speed, 299rpm. Compared with unextruded pomace, SDF fraction in extrudate had a higher level of uronic acid. Furthermore, the extrusion process improved the physicochemical properties of extrudate, increasing the water-holding capacity, swelling, water solubility index, and cation-exchange capacity and decreasing the oil-holding capacity.